Political communication in Asia - Willnat, Lars, 1964-; Aw, Annette (LEA's communication series., 2009)
This edited volume provides a critical review of political communication research conducted in Asia over the past 20 years. Each chapter focuses on studies published in a specific Asian country, selected according to the level of contribution made to the field of political communication in Asia.